Absorption Spectrum of Hydroperoxymethyl Thioformate: A Computational Chemistry Study - David Catalán-Fenollosa; Javier Carmona-García; Ana Borrego-Sánchez; Alfonso Saiz-Lopez; Daniel Roca-Sanjuán (Molecules)
Hydroperoxymethyl thioformate (or HPMTF) is a compound relevant to the chemistry of sulfur in the marine atmosphere. The chemical cycling of this molecule in the atmosphere is still uncertain due in part to the lack of accurate knowledge of its photolytic behavior. Only approximations based on the properties of its chromophores are used in previous studies. In this work, we calculated the absorption spectra of the molecule in gas and aqueous phases using the Nuclear Ensemble Approach (NEA) and the CASPT2 method. Furthermore, we used such information to obtain relative photolysis rates. We found that the chromophore approximation overestimates the photolysis rates in the gas phase by twice the value obtained with the NEA-CASPT2 protocol. Furthermore, for the aqueous phase, we predict a lower role of photolysis as compared to the gas phase.